Dynamics of Canadian Oil Price and its Impact on Exchange Rate and Stock Market. - Alzyoud, Hussein; Wang, Eric Zengxiang; Basso, Michael Glenn (International Journal of Energy Economics and Policy, 2018)
The objective of this study is to analyse the impact of crude oil prices (COP) on exchange rate and stock market returns in Canada for the period of 1986–2015. The results of the study suggest that there was no cointegration among COP, exchange rate and stock market returns. Regression analysis shows that COP and exchange rate, and their variations have a positive and significant impact on the Canadian stock market returns. Policy implications are also discussed. Keywords: Stock Market, Crude Oil, Exchange Rate, Rolling, OLS, DOLS, GARCH. JEL Classifications: L71, Q47, Q48